Concrete Sawing Waste Recycling As Microfiller in Concrete Production (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The main idea of the presented work is to find the ways of recycling the sawing waste/sludge in production of the new concrete. The aim of the study is to examine application of the dust-water suspension as micro filler in self-compacting concrete. In the process of sawing concrete elements a lot of dust waste is produced, the average amount being approximately 0.5-1% of the total amount of concrete. To avoid dust pollution in a production plant the sawing process is accompanied by a water stream, as a result, concrete dust as dust-water suspension is stored in special reservoirs. Recycling of such concrete dust suspension and its utilization as a material pose a significant challenge.